Parental Variables Determining Pre-schoolers' Access to Early Childhood Education in Kenya - Mainye, Momanyi J. (JOOUST, 2018)
Access and engagement to early childhood education worldwide helps prepare young children to succeed in school and become better citizens. The major challenge in Kenya is that Early Childhood Education (ECE) is left in the hands of the community and parents, resulting in a big variation in type and quality of ECE. Even with ECE being devolved to the county government, access to preschool education continues to be a challenge. Hence, the present study explored selected parental variables as determinants of pre-schoolers’ access to early childhood education in Kenya. The study was specifically set to achieve the following objectives: to find out the implication of family socio-economic factors on access to early childhood education, to examine the implication of parental engagement on access to early childhood education, to find out the implication of Parental expectations on access to early childhood education and to find out the implication of parental attitude on access to early childhood education. The study adopted a concurrent triangulation research design within a mixed methods approach and was informed by Bronfenbrenner's Ecological Systems Theory (1979) and supported by Emile Durkeim's Functional Theory (1858-1916). The target population included 21 head teachers, 228 ECE lead teachers and 863 parents and a sub• county director of education. The sample size was 9 head teachers, 43 ECE lead teachers, 76 parents and a sub-county director of education. The instruments of data collection were questionnaires and interview schedules. Validity and reliability of the instruments was enhanced through piloting and expert judgement by staff at the school of Education. Quantitative data was analysed using descriptive statistics and presented in form of tables, graphs and percentages. Qualitative data was analysed using thematic analysis. The findings of the study revealed that Socio-economic status and the level of parents' education are significant in determining pre-schoolers' access to early childhood education. Parents' engagement in children's academic work and school activities was also a predictor of pre-schoolers' access to preschool. Further, parental engagement and parental expectations also had an influence in access to ECE. However, Parents’ attitude proved to have a weak positive relationship to accessibility to pre-school education. It was concluded that the higher the level of education of parents, the higher the chances their children have to access preschools. It was also concluded that more parental engagement was required to make school accessibility easier and to improve the quality of children's education. It was further concluded that high parental expectations can create differences in children’s accessibility to pre-school. This means that children’s access to preschools improves with the improvement of parents’ normal positive expectations from pre• school education. Parents' attitude towards ECE was not a strong determinant of children's accessibility to preschool, because the parents who were identified as having negative attitudes to education were driven by poverty. The present study recommends that; parents should sacrifice in engaging with education of their children. Parents are advised not to have unrealistic expectations from ECE within a short time. The government should financially support children whose parents are financially unstable. The study may be significant in assisting stakeholders in ECE such as parents, teachers and ECE Directors find ways of improving parental participation in ECE.
Keywords: Parental.; Variables determining Pre-Schoolers.; Early Childhood Education.; Kenya.